Endocannabinoid System in Pregnancy Maintenance and Labor: A Mini-Review - Kozakiewicz, Melissa L.; Grotegut, Chad A.; Howlett, Allyn C. (Frontiers in Endocrinology, 2021)
The endocannabinoid system (ECS) is a cell-signaling system present in multiple organ systems and is an integral part of sustaining the microenvironment necessary for early pregnancy success and maintenance. It plays a significant role in embryo development, transport and implantation as well as placentation. The current theory behind the initiation of term labor is that it is a complex, multifactorial process involving sex steroid hormones, prostaglandin production and interplay at the maternal-fetal interface resulting in increased expression of receptors and gap junctions that promote uterine activation. There is increasing evidence that, in addition to early pregnancy events, the ECS plays a regulatory role in pregnancy maintenance and the timing of labor. This review presents an overview of the ECS in pregnancy that focuses on late gestation and parturition.